Treat-to-target (T2T) recommendations for gout. Issue 4 (22nd September 2016) - Kiltz, U; Smolen, J; Bardin, T; Cohen Solal, A; Dalbeth, N; Doherty, M; Engel, B; Flader, C; Kay, J; Matsuoka, M; Perez-Ruiz, F; da Rocha Castelar-Pinheiro, G; et al.
Abstract : Objectives: The treat-to-target (T2T) concept has been applied successfully in several inflammatory rheumatic diseases. Gout is a chronic disease with a high burden of pain and inflammation. Because the pathogenesis of gout is strongly related to serum urate levels, gout may be an ideal disease in which to apply a T2T approach. Our aim was to develop international T2T recommendations for patients with gout. Methods: A committee of experts with experience in gout agreed upon potential targets and outcomes, which was the basis for the systematic literature search. Eleven rheumatologists, one cardiologist, one nephrologist, one general practitioner and one patient met in October 2015 to develop T2T recommendations based on the available scientific evidence. Levels of evidence, strength of recommendations and levels of agreement were derived. Results: Although no randomised trial was identified in which a comparison with standard treatment or an evaluation of a T2T approach had been performed in patients with gout, indirect evidence was provided to focus on targets such as normalisation of serum urate levels. The expert group developed four overarching principles and nine T2T recommendations. They considered dissolution of crystals and prevention of flares to be fundamental; patient education, ensuring adherence to medications and monitoring of serum urate levels were also considered to be of major importance. Conclusions: This is the first application of the T2T approach developed for gout. Since no publication reports a trial comparing treatment strategies for gout, highly credible overarching principles and level D expert recommendations were created and agreed upon.